Fibroblast growth factors induce hepatic tumorigenesis post radiofrequency ablation - Markezana, Aurelia; Paldor, Mor; Liao, Haixing; Ahmed, Muneeb; Zorde-Khvalevsky, Elina; Rozenblum, Nir; Stechele, Matthias; Salvermoser, Lukas; Laville, Flinn; Goldmann, Salome; Rosenberg, Nofar; Andrasina, Tomas; et al. (Scientific reports, 2023)
Image-guided radiofrequency ablation (RFA) is used to treat focal tumors in the liver and other organs. Despite potential advantages over surgery, hepatic RFA can promote local and distant tumor growth by activating pro-tumorigenic growth factor and cytokines. Thus, strategies to identify and suppress pro-oncogenic effects of RFA are urgently required to further improve the therapeutic effect. Here, the proliferative effect of plasma of Hepatocellular carcinoma or colorectal carcinoma patients 90 min post-RFA was tested on HCC cell lines, demonstrating significant cellular proliferation compared to baseline plasma. Multiplex ELISA screening demonstrated increased plasma pro-tumorigenic growth factors and cytokines including the FGF protein family which uniquely and selectively activated HepG2. Primary mouse and immortalized human hepatocytes were then subjected to moderate hyperthermia in-vitro, mimicking thermal stress induced during ablation in the peri-ablational normal tissue. Resultant culture medium induced proliferation of multiple cancer cell lines. Subsequent non-biased protein array revealed that these hepatocytes subjected to moderate hyperthermia also excrete a similar wide spectrum of growth factors. Recombinant FGF-2 activated multiple cell lines. FGFR inhibitor significantly reduced liver tumor load post-RFA in MDR2-KO inflammation-induced HCC mouse model. Thus, Liver RFA can induce tumorigenesis via the FGF signaling pathway, and its inhibition suppresses HCC development.
Keywords: Animals; indukovaná hypertermie; fibroblastové růstové faktory; Cytokines; Hyperthermia, Induced; hepatocelulární karcinom; Catheter Ablation; cytokiny; Fibroblast Growth Factors; lidé; nádory jater; Carcinoma, Hepatocellular; Mice; katetrizační ablace; Carcinogenesis; myši; karcinogeneze; Liver Neoplasms; radiofrekvenční ablace; Radiofrequency Ablation; zvířata; Humans